Implementasi Pembelajaran Berdiferensiasi pada Materi Sejarah Kelas IV SD di Kota Bandar Lampung - Siska, Yulia (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2024)
This study aims to analyze the application of differentiated learning in History learning in Grade IV Elementary School. The research method used is descriptive by describing objects according to the reality that occurs. This research was conducted at State Elementary School 1 Tanjung Senang Bandar Lampung. The steps for implementing this research are arranged in four stages, namely planning, implementation, observation and reflection. The data analysis technique used is to describe facts or realities according to the data obtained regarding the implementation of differentiated learning in the classroom. The results of the study indicate that differentiated learning in the subject of Science and History material for grade IV of State Elementary School 1 Tanjung Senang Bandar Lampung City is implemented in stages to adjust learning based on students' learning needs.